Application of Indigenous Bacterial Formulation of Salt-Washing Wastewater (Bittern) in Degrading Plastic Waste - Ardani, Aliefia Miftakhul; Saputri, Wahyu Dwi; Junaedi, Abdus Salam; Triajie, Haryo (Airlangga Journal of Innovation Management, 2024)
The accumulation of plastic waste can lead to environmental changes. One solution to reduce plastic waste is through a biodegradation process involving microorganisms or bacteria. One solution is biodegradation by using microorganisms or bacteria to break down plastic. Biodegradation is a solution to reduce plastic numbers with the help of microorganisms or bacteria. This study aims to measure the Optical Density (OD), Total Plate Count (TPC), and degradation effectiveness of indigenous bacteria from salt wash wastewater (bittern) in degrading plastic on Nutrient Broth (NB) media with 1% glucose. The research process included sterilization of tools and materials, sampling, media preparation, rejuvenation of bacterial cultures, inoculation, OD measurement, TPC calculation, and percentage of plastic weight loss. Data on OD and TPC were analyzed quantitatively with visual aids. The plastic degradation percentage was measured after 7 days of incubation. The percentage of plastic degradation was measured after 7 days of incubation. The results showed that the highest OD value was bacteria BB8 which amounted to 1.614. TPC for plastic degradation was highest in BB9 which amounted to 13.37 Log CFU/g. BB4 showed the highest percentage of plastic dry weight reduction 36.4% after 7 days. These findings highlight the potential of salt-washing wastewater bacteria for plastic waste degradation.